2022
DOI: 10.1111/1750-3841.16019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of freezing‐assisted treatment on the formation of stable VII‐type complex of fried sweet potato starch and its mechanism

Abstract: To comprehensively understand the effect of freezing‐assisted treatment on the physicochemical properties of the fried sweet potato starch, the structural changes at granular and crystalline level were investigated. The results suggested that the freezing temperature exerted a significant effect on the interactions between sweet potato starch (SPS) and fried oil. With decreasing the freezing‐assisted temperature, the gelatinization enthalpy of the fried frozen SPS remarkably increased by 1.5–4.9 J·g−1 and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…According to the study of Li et al. (2022), the higher peak temperature ( T P ) indicated the formation of starch–lipid complexes with higher crystallinity. Previous studies reported that starch was prone to forming V6‐type complexes with fatty acids, which were divided into two types.…”
Section: Resultsmentioning
confidence: 99%
“…According to the study of Li et al. (2022), the higher peak temperature ( T P ) indicated the formation of starch–lipid complexes with higher crystallinity. Previous studies reported that starch was prone to forming V6‐type complexes with fatty acids, which were divided into two types.…”
Section: Resultsmentioning
confidence: 99%